Framework for heterogeneous data management: An application case in a NoSQL environment from a Climatological Center - Jiménez Galina, Alicia Margarita; Maldonado-Macías, Aide Aracely; Olmos Sanchez, Karla Miroslava; HERNANDEZ-HERNANDEZ, JESUS; Estrada Saldaña, José Fernando; Vazquez-Galvez, Felipe (2024)
Processing, visualizing and understanding data from meteorological networks can present several challenges due to the variety and complexity of the data and must be accessible in real time and in different formats, protocols and standards. This paper presents the development of an innovative technological framework for handling heterogeneous climatological data in a NoSQL environment. The framework was developed following the Action Research methodology and enables the extraction of heterogeneous data, their homogenization, and the creation of a dataset. Its real-case application took place in data repositories used for climatological data management in a specialized regional center in Ciudad Juarez, Mexico. The ´ main repository use MongoDB and contain 631,202 documents with data from several meteorological stations. A 70% reduction in data processing time is evidence that the methodology and framework developed were effective in the case of the application. In addition, the generated data sets are homogenized and in formats compatible with advanced analysis tools.